POTENSI EKONOMI DESA MENUJU DESA MANDIRI (Studi di Desa Sukamanah Kecamatan Karangtengah Kabupaten Cianjur) - Husaeni, Uus Ahmad (JE (Journal of Empowerment), 2017)
The purposes of this study are to describe the economic potential of the village to an independent village, and to determine the factors that support and inhibit encountered in developing of the economic potential ofSukamanah Village. The qualitative method was used in this study an interactive model was used as data analysis techniques. The results show that there are six sectors of the economic potential of rural village in Sukamanah; agriculture, fishery, trading, farming and forestry, animal husbandry and creative economy. Meanwhile, the main supporting factors are the infrastructure condition and the establishment of farmer groups (gapoktan). The inhibiting factors are: the vast majority of farmers in the village of Sukamanah who are not as the land owner, but as a laborer; there is almost no regeneration of farmers; the number of farm workers decreased each year; the distribution of crops farmers cannot be directly sold into the market but it must pass through a broker; and the reduction of productive land in the village of Sukamanah.Â